The economic toll of COVID‐19: A cohort study of prevalence and economic factors associated with postpartum depression in Kenya. Issue 1 (24th February 2022) - Sudhinaraset, May; Landrian, Amanda; Mboya, John; Golub, Ginger
Abstract: Objective: The aim of the study is to examine the risk of postpartum depression (PPD) among women who delivered during the COVID‐19 pandemic compared to women who delivered before the COVID‐19 pandemic and how economic challenges are associated with PPD. Methods: Data were collected from 2332 women. This includes 1197 women from healthcare facilities in 2019 who were followed up at 2–4 and 10 weeks postpartum. Additionally, we recruited 1135 women who delivered from March 16, 2020 onward when COVID‐19 restrictions were mandated in Kenya in the same catchment areas as the original sample to compare PPD rates. Results: Adjusting for covariates, women who delivered during COVID‐19 had 2.5 times higher odds of screening positive for PPD than women who delivered before COVID‐19 (95% confidence interval [CI] 1.92–3.15). Women who reported household food insecurity, required to pay a fee to cover the cost of PPE during labor and delivery and/or postnatal visit(s), and those who reported COVID‐19 employment‐related impacts had a higher likelihood of screening for PPD compared to those who did not report these experiences. Conclusion: The COVID‐19 pandemic has greatly increased the economic vulnerability of women, resulting in increases in PPD. Abstract : The COVID‐19 pandemic has greatly increased the economic vulnerability of women and has increased PPD.